UJI AKURASI MODUL KWH METER DIGITAL PZEM-004T BERBASIS PENGENDALI DIGITAL ESP32 - Prabowo, Yani; Narendro, Arsanto; Wisjhnuadji, TW; Siswanto, Siswanto (SKANIKA: Sistem Komputer dan Teknik Informatika, 2023)
Measurement of electrical energy consumption is very important for everyday life as well as in the industrial sector. As it is known that this amount of energy is the basis for calculating the cost of using electrical energy in kWh units, so that later it will appear in the payment bill. However, this important information is very impractical and inconvenient if to see the amount of the bill, we have to check directly on the KWH meter that is mounted on the wall, and this becomes impractical with a large number of electricity meters. Therefore an IoT-based KWH measurement system is designed that allows monitoring of KWH quantities to be carried out mobile or even remotely via the internet network in a dashboard, making it more practical and efficient. The main components consist of the PZEM-004T module which functions as a measure of AC current and AC voltage used by the load, while the ESP32 module processes the results of measurements made by PZEM-004T and then connects to a computer so that the measured values ​​can appear by PZEM- 004T. The results obtained show that the accuracy of the current and load voltage measurement results, when compared with the results of manual measurements using a digital voltmeter and ammeter, shows a difference of below one percent, meaning that the results of remote measurements with the PZEM-004T provide a good accuracy value.